THE PROBLEM SOLVING IN THE SAO PAULO MATHEMATICAL CURRICULUM AND IN THE CADERNO DO ALUNO - Rossetto, Daniela Zanardo [UNESP] (2021)
In this paper we stablished an analysis about the treatment given to Problem Solving in the Mathematics Curriculum of the State of Sao Paulo and the material Caderno do Aluno, in High School. For the analysis of the Curriculum we used the methodology of Documentary Analysis and for the analysis of the Caderno do Aluno we performed a survey of the problems that compose the material and then we used the Matrix of Process Assessment to establish a qualitative analysis on the given approach to solving problems in this material. The data obtained show that, although the Sao Paulo State Curriculum emphasizes the importance of the development of problem solving skills and emphasizes problematization as a good teaching strategy for the development of certain personal competences, the Caderno do Aluno material presents few problems and, consequently, offers few opportunities that in fact allow the development of the capacity to inquire and ask.